Can Physics Make Us Free? - Pernu, Tuomas K. (Frontiers in Physics, 2017)
A thoroughly physical view on reality and our common sense view on agency and free will seem to be in a direct conflict with each other: if everything that happens is determined by prior physical events, so too are all our actions and conscious decisions; you have no choice but to do what you are destined to do. Although this way of thinking has intuitive appeal, and a long history, it has recently began to gain critical attention. A number of arguments have been raised in defense of the idea that our will could be genuinely free even if the universe is governed by deterministic laws of physics. Determinism and free will have been argued to be compatible before, of course, but these recent arguments seem to take a new step in that they are relying on a more profound and concrete view on the central elements of the issue, the fundamental laws of physics and the nature of causal explanation in particular. The basic idea of this approach is reviewed in here, and it is shown how a careful analysis of physics and causal explanation can indeed enhance our understanding of the issue. Although it cannot be concluded that the problem of free will would now be completely solved (or dissolved), it is clear that these recent developments can bring significant advancement to the debate.